Global economy returning to its recovery course after summer setbacks - Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Frederik Kurcz (DIW Weekly Report, 2021)
Recently, the coronavirus pandemic has caused economic developments in major economies to drift apart: While infection rates were declining and production was experiencing strong growth in places such as Europe and the United States in the second quarter of 2021, emerging economies were experiencing strict economic restrictions due to high case numbers. In some of these countries, the economy declined. Globally, the spread of the coronavirus slowed considerably in late summer 2021 and accordingly, the global economy will return to its recovery course beginning in the third quarter of 2021. Although higher case numbers are expected in winter 2021/22, they will probably have far less of an impact on the economy than before due to increased vaccination rates and selectively implemented containment measures. Positive momentum, particularly in the services sector, will be provided mainly by continued strong growth in private consumption, which is likely to remain a key growth driver in the coming years. Currently, raw material and input shortages are hindering growth in the manufacturing industry. However, disruptions to international supply chains and restrictions at key primary product manufacturing sites are expected to dissipate in the first half of 2022. This will probably lead to some catch-up effects in the manufacturing sector, which is likely to provide the global economy with additional momentum. Thus, DIW Berlin is maintaining its growth forecast of 6.7 percent for the global economy. In 2022, global economic output is expected to grow by 5.2 percent. In the second quarter of 2021, the estimate was 0.3 percentage points lower. Global economic output is expected to grow by 4.2 percent in 2023.
Keywords: E32; E66; F01; 330; Business cycle forecast; economic outlook